PENGARUH KETINGGIAN DI ATAS TANAH DAN JARAK DARI EMPULUR TERHADAP BERAT JENIS DAN KADAR AIR KAYU AFRIKA (KHAYA ANTHOTHECA C.DC.) - Suparman Nurwati; Edi Sarwono (Jurnal Penelitian Hasil Hutan, 1988)
Khaya anthotheca  C.DC. is  one  of  exotic tree  species  selected   for   trial planting   in  Indonesia   by  the  Forest Research  Institute,   about  25 years  ago.This  paper discusses   the   result  of  a   laboratory   study   on   the  variation  of  wood   moisture content and  air dry specific   gravity   within   and  between  trees,  the  effects   of  height   from   the  ground  and  distance   from  pith   outward   on these  two  properties.   The  material for the  study   consisted   of  three  20  year  old  trees  of  Khaya  anthotheca  C.DC.  with  diameters   at breast  height  ranging from  38 - 41 cm, height  (until  top)  15 - I 7 m and clear bole length  from 9 -  9.5  meters.  The  trees were   felled  on plantation  site  at Cikole  (North  of  Bandung)   on  the  slope  of Mount Tangkuban  Perahu,  and  transported to  Bogor  for  laboratory testing.The  result  of  statistical   analyses  reveal,  non  significant   differences between trees  and  bolts  within   trees  for  air dry  specific  gravity,  and significant  difference   in the property   from  pith  outward.The  green   (fresh)  moisture  contents   on  the  other  hand  between   bolts  and  distance   from  pith  are significantly different. Regressions  relating the two properties  (air dry specific  gravity  and moisture  content)  as dependent variables with respective distance from pith   outward   being  1/3, 2/3, and  3/3  of the  radius,  and height  of  bolt  0.2, 2.7, 5.2, and 7.7 meters  above  the ground  as independent variables show  the following  :(1).S  =  0.436  -  0.017Z  +  0.003 Z2                                       =  (R=0.536)                       (Z =Height,   S =Specific gravity)(2).A =  99.98  -   3.591Z  + 0.224 Z2                                        = (R=0.466)                    (Z = Height,  A  = Moisture  content)(3).S =  0.396  + 0.018   X  + 0.044X2                                      =  (R=0.510) (4).A=  86.79  -   1.495  x   + 4.25X2                                         =  (R=0.101)               (X = distance  from  pith  outward)Test  of  significance  of  the  regression coeficient   (Table  4)  indicate  significant  F values for  the  first  two  equations (effect  of height)  and non significant  results for  the last two equations (effect  of distance  from pith).